A validation study of a noninvasive lactate threshold device - McMorries, R. M.; Joubert, D. P.; Jones, E. J.; Faries, M. D. (International Journal of Exercise Science, 2019)
The lactate threshold is considered a key marker of endurance exercise performance and identification of this threshold is important in writing an exercise training program. Unfortunately, assessment of the lactate threshold has traditionally required venous or capillary blood samples and a specialized meter to assess blood lactate concentrations. Recently, a consumer grade, non-invasive device was developed to determine muscle oxygenation and estimate the lactate threshold. Purpose: The aim of this study was to assess the validity of a noninvasive lactate threshold device (NID) to determine lactate threshold heart rate (LTHR). Methods: Twenty-one recreational athletes (14 females, 39 ± 7 years, 29.1 ± 5.2% fat, 37.8 ± 6.0 ml·kg-1·min-1; 7 males, 42 ± 9 years, 16.8 ± 2.2% fat, 45.9 ± 6.4 ml·kg-1·min-1) completed a personalized graded exercise test on a treadmill. All participants wore the NID and blood lactate samples were taken at the end of 3-minute stages. LTHR was then calculated using two traditional methods (4 mmol/L and >1 mmol/L increase) and compared against the same heart rate values calculated by the NID. Results: No significant differences (p = .87) were found in LTHR between the NID and the traditional lactate methods (NID: 167 ± 9 bpm, 4 mmol/L: 167 ± 12 bpm, >1 mmol/L: 167 ± 12 bpm). Conclusions: This study provides preliminary support for the validity of the NID for estimation of LTHR.